DOI: 10.14264/uql.2019.653
|View full text |Cite
|
Sign up to set email alerts
|

A pan genome reverse vaccinology approach to prevent Streptococcus agalactiae infection in farmed tilapia

Abstract: Streptococcus agalactiae (Group B Streptococcus; GBS) is a Gram-positive pathogenic bacterium that causes disease in a wide range of animals including fish. Outbreaks of GBS in farmed fish have substantial economic impacts on the aquaculture industry, especially in tilapia production, a staple food product in tropical and subtropical low-and middle-income countries and the second most widely farmed fish after carp. Although vaccination can effectively prevent disease caused by GBS in fish it often fails after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 261 publications
0
2
0
Order By: Relevance
“…For example, GBS may not be recognized by vaccine‐induced antibodies if the respective antigens, particularly surface‐anchored proteins, are masked by bacterial capsular polysaccharides or not expressed properly at the stage of bacterial colonization/proliferation. Kawasaki (2019) reported that, despite the strong antibody responses in Nile tilapia, the recombinant adhesins (discovered by the RV approach) were unable to induce protection from a lethal challenge, which is likely due to the post‐transcriptional processing of adhesins and antigen masking by the bacterial capsule. Therefore, accurate prediction of genuine protective antigens, in silico or in vitro, is undoubtedly crucial to leverage the efficacy of the antigen discovery framework.…”
Section: Contribution Of Genomics To the Development Of Novel Strepto...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, GBS may not be recognized by vaccine‐induced antibodies if the respective antigens, particularly surface‐anchored proteins, are masked by bacterial capsular polysaccharides or not expressed properly at the stage of bacterial colonization/proliferation. Kawasaki (2019) reported that, despite the strong antibody responses in Nile tilapia, the recombinant adhesins (discovered by the RV approach) were unable to induce protection from a lethal challenge, which is likely due to the post‐transcriptional processing of adhesins and antigen masking by the bacterial capsule. Therefore, accurate prediction of genuine protective antigens, in silico or in vitro, is undoubtedly crucial to leverage the efficacy of the antigen discovery framework.…”
Section: Contribution Of Genomics To the Development Of Novel Strepto...mentioning
confidence: 99%
“…Furthermore, antigenic proteins detected by 'traditional RV' do not necessarily convey protective immune responses in vivo for various reasons. For example, GBS may not be recognized by vaccine-induced antibodies if the respective antigens, particularly surface-anchored proteins, are masked by bacterial capsular polysaccharides or not expressed properly at the stage of bacterial colonization/proliferation Kawasaki (2019). reported that, despite the strong antibody responses in Nile tilapia, the recombinant adhesins (discovered by the RV approach) were unable to induce protection from a lethal challenge, which is likely due to the post-transcriptional processing of adhesins and antigen masking by the bacterial capsule.…”
mentioning
confidence: 99%